If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 72 = -3x Reorder the terms: 72 + 5x = -3x Solving 72 + 5x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 72 + 5x + 3x = -3x + 3x Combine like terms: 5x + 3x = 8x 72 + 8x = -3x + 3x Combine like terms: -3x + 3x = 0 72 + 8x = 0 Add '-72' to each side of the equation. 72 + -72 + 8x = 0 + -72 Combine like terms: 72 + -72 = 0 0 + 8x = 0 + -72 8x = 0 + -72 Combine like terms: 0 + -72 = -72 8x = -72 Divide each side by '8'. x = -9 Simplifying x = -9
| (3x-2)/(24x-17) | | 5x+72=-3 | | 5(a+5)=60 | | 34=5c-6 | | 5y+3x=8 | | q+7= | | 2e-9=1 | | 20=5x+5 | | 3/2q=2/8 | | -2=m(-3)+b | | v+(-32.5)+(v+25.7)=198.7 | | 9n=5 | | 15+13=1218 | | 2x^2+8x-24=936 | | -400x+4000.00=2400.00 | | -16t^2+96t=0 | | -400x-4000.00=2400.00 | | 117-7x=11x+23 | | 3x/4+3=6 | | .1x+.25(x-12)=11 | | 16/15x-45+5/x-3 | | -400.00x-4000.00=0.00 | | -9/13w=3/10 | | v+(v-32.5)+(v+25.7)=193.4 | | 9=(9x-4)(x-6)(x^2-8)(x+4) | | 3x+(1/5)=(1/4) | | y=(x+2)2+2 | | 2c+2c+2+c=107 | | 6x^2+14x-30=0 | | 2/7f=5/7 | | X/2=0.6 | | 525+.21c=585+.13c |